The hunters - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Brotherband chronicles, 2012)
Determined to recover the Adomal and to prevent the pirate Zavac from doing more damage, Hal and his brotherband crew persue Zavac to the lawless fortress of Ragusa where, if Hal is to succeed, he will have to go beyond his brotherband training and face the pirate one-on-one in a fight to the finish.